Judicial Oversight of Administrative Decisions Based on Artificial Intelligence - houchat , Fouzia (Journal of Human Sciences, 2025)
In the context of societal transformation, developed countries are keen on utilizing artificial intelligence in decision-making within public administration. These intelligent systems assist in decision-making, and in most cases, their decisions are free from errors and biases. These decisions are referred to by various names, such as algorithmic administrative decisions or automated administrative decisions. This type of decision, like other traditional administrative decisions, is subject to scrutiny for its legality to ensure that all necessary conditions for its validity are met. Since it is an administrative decision issued through artificial intelligence, the role of the administrative judge is to ensure that the algorithmic system processes the data with high quality, thereby achieving the required transparency and ensuring that the issued administrative decisions meet the expectations of both the administration and the decision’s recipient.